2015
DOI: 10.1136/thoraxjnl-2014-206070
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training decreases bronchial hyperresponsiveness and systemic inflammation in patients with moderate or severe asthma: a randomised controlled trial

Abstract: BackgroundThe benefits of aerobic training for the main features of asthma, such as bronchial hyperresponsiveness (BHR) and inflammation, are poorly understood. We investigated the effects of aerobic training on BHR (primary outcome), serum inflammatory cytokines (secondary outcome), clinical control and asthma quality of life (Asthma Quality of Life Questionnaire (AQLQ)) (tertiary outcomes).MethodsFifty-eight patients were randomly assigned to either the control group (CG) or the aerobic training group (TG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
167
0
39

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(211 citation statements)
references
References 34 publications
5
167
0
39
Order By: Relevance
“…In the study by França-Pinto et al [19], patients exercised for 30 min two times/w for 3 months on a treadmill at intensities between 60 and 80% of HRmax. The average improvement in VO 2 max was ~3.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by França-Pinto et al [19], patients exercised for 30 min two times/w for 3 months on a treadmill at intensities between 60 and 80% of HRmax. The average improvement in VO 2 max was ~3.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise has been shown to be a beneficial factor in the control of asthma [11]. Physical exercise reduces systemic and bronchial inflammation, and increases maximal oxygen uptake [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms through which exercise training improves exertional symptoms could relate to improving peripheral muscle conditioning, improved emotional wellbeing, modification of dyspnoea perception, or a disease-modifying effect of exercise on asthma. For example, a more recent trial found that 12 weeks of aerobic training improved bronchial hyperresponsiveness, inflammatory markers and patient-reported asthma control and quality of life, with particular improvement in the Activity Limitation domain on the AQLQ [109].…”
Section: Inhaled Corticosteroids and Dyspnoeamentioning
confidence: 99%